Conservation of the binding site for the arginine repressor in all bacterial lineages - Makarova, Kira S (BioMed Central, 2001)
BACKGROUND: The arginine repressor ArgR/AhrC is a transcription factor universally conserved in bacterial genomes. Its recognition signal (the ARG box), a weak palindrome, is also conserved between genomes, despite a very low degree of similarity between individual sites within a genome. Thus, the arginine repressor is different from two other universal transcription factors - HrcA, whose recognition signal is very strongly conserved both within and between genomes, and LexA/DinR, whose signal is strongly conserved within, but not between, genomes. The arginine regulon is well studied in Escherichia coli and to some extent in Bacillus subtilis and some other genomes. Here, we apply the comparative genomic approach to the prediction of the ArgR-binding sites in all completely sequenced bacterial genomes. RESULTS: Orthologs of ArgR/AhrC were identified in the complete genomes of E. coli, Haemophilus influenzae, Vibrio choleras, B. subtilis, Mycobacterium tuberculosis, Thermotoga maritima, Chlamydia pneumoniae and Deinococcus radiodurans. Candidate arginine repressor binding sites were identified upstream of arginine transport and metabolism genes. CONCLUSIONS: We found that the ArgR/AhrC recognition signal is conserved in all genomes that contain genes encoding orthologous transcription factors of this family. All genomes studied except M. tuberculosis contain ABC transport cassettes (related to the Art system of E. coli) belonging to the candidate arginine regulons.